Au and Pt Diffusion in Electrodeposited Amorphous Sb2Te3 Thin Films. Issue 9 (29th January 2021) - Ihalawela, Chandrasiri A.; Sundararajan, Mayur; Cooper, Kevin W.; Kordesch, Martin E.; Ingram, David C.; Lin, Xiao-Min; Chen, Gang
Abstract : Amorphous Sb2 Te3 thin films are synthesized using electrodeposition in different thicknesses to explore their solid electrolytic nature with respect to some noble metals. Au and Pt are used as the substrate materials and thermally diffused into the Sb2 Te3 films under passivated and nonpassivated conditions. Rutherford backscattering spectrometry is used to study the Au and Pt diffusion into the films as a function of depth. It is found that Au diffuses into the Sb2 Te3 thin films even at room temperature. In contrast, there is no observable diffusion of Pt at room temperature. At a higher temperature (i.e., 200 °C), both Au and Pt diffuse into the Sb2 Te3 thin films and Au diffusion is more significant than Pt. The findings suggest that amorphous Sb2 Te3 can be used as a good solid electrolyte to permit the diffusion of some noble metals such as Au and Pt. Abstract : Solid electrolytic nature of electrodeposited Sb2 Te3 is studied with respect to the diffusion of Au and Pt precious metals. Au/Sb2 Te3 /Au/SiO2 and Pt/Sb2 Te3 /Pt/SiO2 thin film systems are synthesized and the compositional depth profiles are characterized using Rutherford backscattering spectrometry. In summary, Au diffusion in amorphous Sb2 Te3 films is more significant than Pt at both room temperature and elevated temperatures.